P2 LOCAL ABDOMINAL VERSUS THORACIC AORTA STIFFENING IN HYPERTENSIVE RATS UNDER EITHER NO RESTRICTION OR SALTED DIET - George Lindesay; Neila Malti; Christophe Ragonnet; Marc Isabelle; Nicole Villeneuve; Yvonnick Bézie; Christine Vayssettes-Courchay (Artery Research, 2017)
Background: Hypertensive humans exhibit reduced nitric oxide bioavailability and increased salt sensitivity, both of which are related to central artery stiffening. We studied the effect of 5 week NO restriction via L-NAME treatment in spontaneously hypertensive rats (SHR) and 5% salted diet in salt-sensitive SHR (SHRSP), on the thoracic (TA) and abdominal (AA) aorta. Methods: Ultrasonic recording of the pulsatile aortic diameter together with blood pressure allowed the measurement of diameter distension and ß-stiffness index. SHRLN and SHRSP salt were compared to their respective control normotensive rats WKY and two measurements were performed in each rat for TA and AA: at operating basal pressure and at reduced WKY matched pressure, n = 6–8. Aortic structure was then characterized by immunohistochemical analysis. Results: At basal blood pressure, stiffness was greatly increased (range 263–330%) and distension decreased at both TA and AA in both models. At WKY-matched blood pressure and pulse pressure, AA parameters remained significantly altered whereas TA recovered to values not significantly different from WKY values. Immunohistochemistry evaluation showed similar increases of markers of fibrosis and remodeling for AA and TA in the two models (fibronectin and its integrin alpha5-beta1 receptor, Focal Adhesion Kinase). Conclusions: This study confirms the potency of ultrasonic derived stiffness measurements and that aortic remodeling is non-uniform along the aortic trunk. The thoracic aorta, which has an important role in dampening cardiac output appears less sensitive to salt loading and NO reduction induced stiffening. Surprisingly, fibrosis does not appear to account for these dynamic differences.